Indonesian pediatricians’ knowledge of Rome IV criteria and their therapeutic approach to infantile colic - Agus Tini Sridevi; Hubert Jonathan; Brahmantyo Ardhi Wicaksono; Badriul Hegar (Paediatrica Indonesiana, 2022)
Background Infantile colic is a functional gastrointestinal disorder (FGID) that occurs in approximately 20% of infants under 6 months. Even though this condition is self-limiting, inappropriate therapy affects the baby’s future quality of life. Therefore, it is essential for physicians, especially pediatricians, to employ a correct diagnosis based on the currently accepted Rome IV criteria and an appropriate therapeutic approach. Objective To assess the gaps in Indonesian pediatricians’ understanding of infantile colic according to Rome IV criteria, their therapeutic approach in managing the condition, and associated factors. Methods We randomly selected 131 pediatricians from the Jakarta Chapter of the Indonesian Pediatric Society to complete a questionnaire aimed at assessing their knowledge on the diagnosis of and therapeutic approach to infantile colic. The questionnaire was scored on a scale of 0 to 20. We evaluated the association between questionnaire scores and their association with several variables, including years of clinical experience, accreditation of pediatric residency institution, type of hospital, and guidelines used. Results Out of the 131 pediatricians selected, 75 (57.3%) had used the Rome IV criteria. The mean knowledge score of those participants was 14.24 (SD 3.32) out of 20. Mean therapeutic approach score of all participants was 11.50 (SD 2.80) out of 16 points. There was no significant association between either knowledge or therapeutic approach score with length of clinical experience, accreditation of pediatric residency institution, hospital type, or guidelines used. Conclusions Most surveyed pediatricians who have used the Rome IV criteria have fairly good knowledge of infantile colic. Overall, pediatricians also have a fairly sound therapeutic approach to infantile colic. However, with mean scores of approximately 70% of the maximum score, education is needed to improve on these areas. Knowledge of and therapeutic approach to infantile colic are not associated with length of clinical experience, accreditation of pediatric residency institution, hospital type, or guidelines used.